Respuesta :

Hello and Good Morning/Afternoon

Let's take this problem step-by-step:

To find the solution to a system of equation

  ⇒ must set the equations equal to each other

     ⇒ and solve

Let's put that into action

  [tex]x^2-2x+3 = -2x + 12\\x^2-2x+2x+3-12=0\\x^2-9=0\\(x+3)(x-3)=0[/tex]

  • At this point, to make the whole thing equal zero

          ⇒ either 'x+3' or 'x-3' equals zero

              ⇒ must find 'x' that satisify either equation

                    [tex]x-3=0\\x=3\\\\x+3=0\\x=-3[/tex]

Let's find the corresponding f(x) to each x-value

  [tex]f(3) = -2(3)+12=-6+12 = 6\\\\f(-3) = -2(-3) + 12=6+12=18[/tex]

Therefore the solutions are (3,6) and (-3,18)

Answer: (3,6), (-3,18)

Hope that helps!

#LearnwithBrainly